Radiotherapy for Vaginal Recurrences of Cervical Cancer in Patients After Prior Surgery: Analysis of Effect and Prognostic Factors - Yan, Junfang; Zheng, Ziye; Zhu, Jiawei; Hu, Ke; Hou, Xiaorong; Shen, Jie; Lian, Xin; Sun, Shuai; Miao, Zheng; Shen, Jing; Guan, Hui; Meng, Qingyu; et al. (Frontiers in Oncology, 2021)
Objective: The role of salvage radiotherapy (RT) in the treatment for vaginal recurrence of cervical cancer in patients after prior surgery remains controversial. The aim of this study was to evaluate the efficacy and toxicity of salvage RT, and explore prognostic factors associated with the survival after recurrence. Methods: Patients with cervical cancer, treated for vaginal recurrences at Peking Union Medical College Hospital between July 2011 and November 2019, were identified. All the patients underwent prior surgery for primary tumor and received salvage RT including external beam radiotherapy (EBRT), brachytherapy (BRT) or both. The irradiation field and dose depended on the conditions of patients. Recurrence patterns were classified into four categories according to the site of recurrence. Prognostic factors on the overall survival (OS), progression-free survival (PFS) and local control (LC) were analyzed, and late toxicity were evaluated. Results: A total of 141 patients were included in the analysis, with a median follow-up time of 40.8 months. The estimated 5-year OS, PFS and LC rates were 81%, 75% and 87%, respectively. In multivariate analysis, endovaginal recurrence and no irradiation history were favorable prognostic factors associated with OS (all p<0.05), PFS (all p<0.05) and LC (all p<0.05). Area under the receiver operating characteristic (ROC) curve (AUC) of recurrence pattern is larger than the stage of primary tumor (0.734 vs. 0.670). Conclusions: RT was an effective treatment with tolerable toxicity for vaginal recurrences of cervical cancer in patients with prior surgery. Recurrence pattern and irradiation history were important prognostic factors.